Endocytic Adaptor Epidermal Growth Factor Receptor Substrate 15 (Eps15) Is Involved in the Trafficking of Ubiquitinated α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid Receptors - Lin, Amy; Man, Heng-Ye (The Journal of biological chemistry, 2014)
AMPA-type glutamate receptors (AMPARs) play a critical role in mediating fast excitatory synaptic transmission in the brain. Alterations in receptor expression, distribution, and trafficking have been shown to underlie synaptic plasticity and higher brain functions, including learning and memory, as well as brain dysfunctions such as drug addiction and psychological disorders. Therefore, it is essential to elucidate the molecular mechanisms that regulate AMPAR dynamics. We have shown previously that mammalian AMPARs are subject to posttranslational modification by ubiquitin, with AMPAR ubiquitination enhancing receptor internalization and reducing AMPAR cell surface expression. Here we report a crucial role for epidermal growth factor receptor substrate 15 (Eps15), an endocytic adaptor, in ubiquitination-dependent AMPAR internalization. We find that suppression or overexpression of Eps15 results in changes in AMPAR surface expression. Eps15 interacts with AMPARs, which requires Nedd4-mediated GluA1 ubiquitination and the ubiquitin-interacting motif of Eps15. Importantly, we find that Eps15 plays an important role in AMPAR internalization. Knockdown of Eps15 suppresses the internalization of GluA1 but not the mutant GluA1 that lacks ubiquitination sites, indicating a role of Eps15 for the internalization of ubiquitinated AMPARs. These results reveal a novel molecular mechanism employed specifically for the trafficking of the ubiquitin-modified AMPARs.